Synthesis, characterization, and photophysical properties of cyclotriphosphazenes containing quinoline-4-aldehyde-p-oxyanil moieties - Ibisoglu, Hanife; Un, Sule Sahin; Erdemir, Eda; Tumay, Sureyya Oguz (Taylor & Francis Ltd, 2021)
In the present work, a series of cyclotriphosphazenes including Schiff bases, {[N3P3(biph)(2)(R)(2)] (5), [N3P3(biph)(R)(4)] (6), and N3P3R6 (7) (biph = 2 ',2 ''-dioxy-1 ',1 ''- biphenyl, R = Quinoline-4-aldehyde-p-oxyanil}, were synthesized in high yields via the nucleophilic substitution reactions of quinoline-4-aldehyde-p-hydroxyanil (1) with [N3P3(biph)(2)Cl-2] (2) and [N3P3(biph)Cl-4] (3) and N3P3Cl6 (4), respectively. The structures of all products (5, 6, and 7) were defined by elemental analysis, mass spectrometry, FTIR, (H-1, C-13, and P-31) NMR spectroscopies. Furthermore, the photophysical properties of these new cyclotriphosphazenes (5, 6, and 7) in different solvents and concentrations were investigated and the results were compared and discussed. The absorption characteristics of novel cyclotriphosphazene-based Schiff bases demonstrated n-pi* and pi-pi* transitions which can be attributed to quinoline side whereas absorbance values were significantly enhanced under the same analytical conditions when the number of quinoline groups attached to the cyclotriphosphazene-core increased. As a result, the molar absorptivity of novel cyclotriphosphazene-based Schiff bases which substituted with two (5) and six quinolines moieties (7) were increased 4.43- and 11.4-fold, respectively, when compared with their precursor (1).
Keywords: Cyclotriphosphazene; phosphazene; quinoline-4-aldehyde-p-hydroxyanil; Schiff base; photophysical properties